The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/jmri.24819
|View full text |Cite
|
Sign up to set email alerts
|

2D phase‐sensitive inversion recovery imaging to measure in vivo spinal cord gray and white matter areas in clinically feasible acquisition times

Abstract: PURPOSE In-vivo assessment of spinal cord gray matter (GM) and white matter (WM) could become pivotal to study various neurological diseases, but it is challenging because of insufficient GM/WM contrast provided by conventional MRI. Here we present and assess a procedure for measurement of spinal cord total cross-sectional area (TCA) and GM areas based on phase sensitive inversion recovery imaging (PSIR). MATERIALS AND METHODS We acquired 2D PSIR images at 3T at each disc level of the spinal axis on 10 healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
71
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 31 publications
(71 citation statements)
references
References 54 publications
0
71
0
Order By: Relevance
“…25,26 Our group recently developed a sensitive method to detect SC GM atrophy based on 2D-PSIR image acquisitions that enable reliable assessment of TCAs, GM and WM structures in clinically feasible scanning times (<2min/level). 27 Using this method, we demonstrated that the upper cervical SC GM can be reduced in RMS in the absence of WM atrophy, and that GM atrophy is substantially more pronounced in PMS compared to RMS. 28 In addition, the cervical SC GM area was inversely correlated with disability.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…25,26 Our group recently developed a sensitive method to detect SC GM atrophy based on 2D-PSIR image acquisitions that enable reliable assessment of TCAs, GM and WM structures in clinically feasible scanning times (<2min/level). 27 Using this method, we demonstrated that the upper cervical SC GM can be reduced in RMS in the absence of WM atrophy, and that GM atrophy is substantially more pronounced in PMS compared to RMS. 28 In addition, the cervical SC GM area was inversely correlated with disability.…”
Section: Introductionmentioning
confidence: 87%
“…Reliability assessments have previously been published for this segmentation methodology. 27 Based on these results, GM and TCA assessments were made by a single reader (RS), who was masked to the clinical data. TCA measurements were performed in a semi-automated fashion.…”
Section: Design and Methodsmentioning
confidence: 99%
“…A number of clinically feasible MRI acquisition protocols have been proposed recently, which allow the clear distinction between GM and WM in the SC . However, their use is currently restricted to the mid‐ and upper SC due to technical challenges associated with imaging lower levels of the SC.…”
Section: Introductionmentioning
confidence: 99%
“…5 A number of clinically feasible MRI acquisition protocols have been proposed recently, which allow the clear distinc-tion between GM and WM in the SC. [6][7][8] However, their use is currently restricted to the mid-and upper SC due to technical challenges associated with imaging lower levels of the SC. For instance, due to the anatomical location of the lower SC, longer examination times are often required in order to achieve sufficient coverage and signal-to-noise ratio (SNR) for high-resolution imaging.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, there were first attempts toward this differentiation using a series of acquisition approaches. [9][10][11][12] More recently an averaged magnetization inversion recovery acquisitions (AMIRA) sequence was proposed, delivering a notable SC GM/WM contrast while maintaining short acquisition times at the same time. 13 The latter is especially important for imaging small-sized structures (like the SC GM/WM) in patients with disabilities having a short time window in which they can lie still.…”
mentioning
confidence: 99%